2014
DOI: 10.1007/s00726-014-1869-x
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional peptides derived from an egg yolk protein hydrolysate: isolation and characterization

Abstract: An egg yolk protein by-product following ethanol extraction of phospholipids (YP) was hydrolyzed with pepsin to produce and identify novel peptides that revealed antioxidant, ACE inhibitory and antidiabetic (α-glucosidase and DPP-IV inhibitory) activities. The peptic hydrolysate of YP was fractionated by ion-exchange chromatography and reversed-phase high-pressure liquid chromatography. Isolated peptides were identified using mass spectrometry (MALDI-ToF) and the Mascot Search Results database. Four peptides o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 31 publications
1
114
1
Order By: Relevance
“…Of particular importance are peptides with multifunctional abilities that can be used in the prevention and treatment of diet-related diseases such as diabetes (Zambrowicz et al 2014). One plant that has been implicated in the management of dietrelated diseases such as hypertension is Citrullus lanatus L. (Arise et al 2016).…”
Section: In Vitro Antioxidant and α-Amylase Inhibitory Properties Of mentioning
confidence: 99%
“…Of particular importance are peptides with multifunctional abilities that can be used in the prevention and treatment of diet-related diseases such as diabetes (Zambrowicz et al 2014). One plant that has been implicated in the management of dietrelated diseases such as hypertension is Citrullus lanatus L. (Arise et al 2016).…”
Section: In Vitro Antioxidant and α-Amylase Inhibitory Properties Of mentioning
confidence: 99%
“…This includes bioactive protein hydrolysates and peptides from egg, meat, marine foods, rice and wheat generated using different enzymes such as Alcalase, Papain, Pepsin etc. (Zambrowicz et al 2015;Mora et al 2014;Harnedy and FitzGerald 2012;Cavazos and Gonzalez de Mejia 2013). However, very few studies have been reported on producing protein hydrolysates and peptides by microbial fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Spirulina diet supplementation increased the feed intake of rabbits, as well as improve the quality of rabbit meat with higher levels of GLA [171]. The green seaweed U. lactuca has been reported as a suitable low-energy, high-protein foodstuff for sheep and goats [172,173]. However, seaweed may be not be suitable for supplementation in pregnant ewes, having been reported to interfere with passive immunity in lambs and increasing mortality rate [174].…”
Section: Ruminantsmentioning
confidence: 99%
“…Cummin seed peptides CSP1, CSP2 and CSP3 have been reported to exhibit cholesterol lowering activity [105], anti-oxidant and anti-amylase activities in vitro [99]. Four other peptides, YINQMPQKSRE, YINQMPQKSREA, VTGRFAGHPAAQ and YIEAVNKVSPRAGQF isolated from egg yolk have been reported to show antidiabetic, ACE inhibitory and antioxidant activities [172]. These peptides could be important in managing metabolic diseases such as diabetes and hypercholesterolemia.…”
Section: Multifunctional Peptidesmentioning
confidence: 99%